A randomized double-blind, placebo-controlled, cross-over trial assessing the effect of tadalafil (Cialis) on the cardiovascular response in men with complete spinal cord injury above the sixth thoracic level: A Pilot Study. (December 2018) - Ethans, Karen; Casey, Alan; Tarhoni, Mohamed; Nankar, Mayur; Entcheva, Stella
Abstract Study design Double-blind, randomized cross-over placebo-controlled pilot study. Objectives To determine the effects of tadalafil on systolic blood pressure (SBP), heart rate (HR), and dizziness of men with American Spinal Injury Association Impairment Scale-A (AIS-A) spinal cord injury (SCI) between cervical-4 (C4) and thoracic-5 (T5) levels. Setting Outpatient rehabilitation clinic. Design Double-blind, randomized cross-over placebo-controlled pilot study. Methods 20 males with AIS-A SCI, C4-T5 received either tadalafil 20 mg or placebo for the first arm, and then were crossed-over after 1 week to the second arm. SBP, HR, and Visual Analogue Scale (VAS) for dizziness upon sitting up from lying were measured at baseline and again 1, 2, 4, 12, 22, 29, and 36 h post dose administration. The change in each outcome measure (SBP, HR, VAS dizziness) was observed from pre-dose to each time point. A change in VAS dizziness of 2 cm or greater (scale 0–10 cm) was considered positive. Results SBP did not change significantly in either group. However, HR increased significantly in the tadalafil group at several time points (12 hp < 0.05, 22 hp <0.05, 29 hp <0.01, and 36 hp <0.05), with no change in the placebo group. The VAS dizziness significantly increased (range 2–6 cm changes) at some time point in 1/4 of the subjects after tadalafil, but not in the placebo group; all reports of dizziness were at 12 h or later. Conclusions Tadalafil use in people with SCI above T6 is safe with respect to not causing hypotension; hemodynamic changes that occurred 12–36 h post administration were compensated for by elevations in HR. Sponsorship The Manitoba Medical Services Foundation and the Health Sciences Centre Foundation.